2019
DOI: 10.1123/japa.2017-0400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Power Output, and Cadence on Energy Expenditure and Lower Limb Antagonist Muscle Coactivation During Cycling

Abstract: It is unknown if higher antagonist muscle co-activation is a factor contributing to higher energy cost of cycling in older adults. We determined how age, power output, and cadence affect metabolic cost and lower extremity antagonist muscle co-activation during submaximal cycling. Thirteen young and 12 older male cyclists completed 6-minute trials at four power output-cadence conditions (75W-60rpm, 75W-90rpm, 125W-60rpm, and 125W-90rpm) while electromyography (EMG) and oxygen consumption were measured. Knee and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…A minimum sample size of 8 participants was needed to achieve a statistical power of 0.8 to detect a large effect size main effect (η2 = 0.601) of pedal spacers on lower extremity joint angles at an alpha level of 0.05. Recreational cyclists were classified as people who self-reported that they had ridden a bicycle for recreation, transportation, and/or exercise throughout the majority of the past year (Buddhadev and Martin 2018). Participants with pain or recent injuries to the lower extremity were excluded.…”
Section: Participantsmentioning
confidence: 99%
“…A minimum sample size of 8 participants was needed to achieve a statistical power of 0.8 to detect a large effect size main effect (η2 = 0.601) of pedal spacers on lower extremity joint angles at an alpha level of 0.05. Recreational cyclists were classified as people who self-reported that they had ridden a bicycle for recreation, transportation, and/or exercise throughout the majority of the past year (Buddhadev and Martin 2018). Participants with pain or recent injuries to the lower extremity were excluded.…”
Section: Participantsmentioning
confidence: 99%